(untitled) (Journal of the College of Basic Education, 2023)
The current research aimed to identify behavioral deviations among middle school students . The current research is determined by middle school teachers, where a random sample of (150) male and female teachers was selected from the city of Baghdad. To achieve the objectives of the research, the researcher prepared a scale to measure behavioral deviations among middle school students The researcher used it to extract the results of the research It reached a set of results, and accordingly the researcher came out with conclusions, recommendations and suggestions.